Synthesis of bioactive calcium phosphate from cockle shell for biomedical applications - Mohd Pu’ad, Nor Atiqah Syafinaz; Te Chuan, Lee; Salman, Nor Syazwani; Selimin, Mohamad Ali; Abdul Latif, Amirul Faiz; Muhamad, Mimi Suliza; Abdullah, Hasan Zuhudi; Idris, Maizlinda Izwana; Mustapha, Siti Noor Hidayah (AMG Transcend Association, 2020)
The present work reports the synthesis of bioactive calcium phosphate from cockle shell via the combination of calcination and hydrothermal process. The raw cockle shells were pre-treated with 30 % of hydrogen peroxide for 4 days to eliminate the impurities. Afterward, the dried cockle shells were crushed and calcined at various temperatures ranging from 300 to 1100 °C. Subsequently, the calcined powders underwent hydrothermal process in di-ammonium hydrogen phosphate and distilled water at pH of 10.5 for 30 minutes. Lastly, the hydrothermal treated powders were dried in oven at 50 °C for 3 days. The results showed that the mixture of aragonite, calcite, hydroxyapatite, and calcium hydroxide was successfully synthesized at a calcination temperature of 900 °C and 1100 °C. In addition, the nanorods in the length of 80-300 nm were formed. The findings of this work indicate that the cockle shell could be transformed into valuable bioactive materials for biomedical applications.